GENERALISED SPACE TIME AUTOREGRESSIVE WITH EXOGENOUS VARIABLE (GSTARX) MODELING WITH INTERVENTIONS ON WORKPLACE MOBILITY AGAINST TOTAL COVID-19 CASES IN FIVE PROVINCES ON JAVA ISLAND - LISTIANI SUSANTO, NADIA
The spread of the Corona virus (SARS-CoV) and the type of disease caused by coronavirus disease 2019 (Covid-19) which was first discovered in the city of Wuhan, China, has a great effect on all fields, especially global health and socio-economic. In Indonesia itself, the policy of Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) has an effect on the cessation of economic activity resulting in reduced mobility, especially in office and industrial sectors. Spatially, the economic structure is dominated by Java Island so it takes a space-time model that is not only influenced by previous observations in the same location and previous observations in different locations, but external factors that can be expressed as exogenous variables. GSTARX is a GSTAR model development model due to the possible influence of other factors other than observations at previous times in the same location or different locations. Intervention is a model used to explain events both internally and externally affecting variables within given period of time. There are two types of interventions, namely step and pulse functions. In this paper, an iterative procedure is introduced in detecting GSTAR, GSTARX, and GSTARX step function intervention models. Obtained model GSTARX (1;1) with the intervention of (????,????,????) for DKI Jakarta, but West Java, Central Java, East Java, DI Yogyakarta with the GSTAR(1;1), which more accurately describes workplace mobility to the total covid-19 cases.